Proses Kreatif Desain Komunikasi Visual E-Magazine Radio PRFM News Channel sebagai Media Promosi - Pangastuti, Nurmareta Labonisa; Ramdani, Guruh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This project examines the development of digital promotional media in the form of an e-magazine for PRFM News Channel Radio, with the goal of increasing audience reach and engagement in the digital era. The uniqueness of this project lies in the integration of the Design Thinking approach by Nigel Cross within the context of local radio media—an area that has rarely been explored in previous studies, which mostly focus on social media or podcasts as the main promotional tools. The method used is a qualitative approach based on Design Thinking stages: Quantify the Problem (identifying PRFM’s low audience engagement on digital channels through observation and interviews with active listeners), Generate Concepts (developing various visual and promotional content ideas), Refine Concepts (testing design preferences with target audience respondents), Select a Concept (choosing the final design based on their feedback), Design, and Present (implementing and publishing the e-magazine). The emagazine was designed with a modern and professional layout using software such as Adobe InDesign. It was published through the Hyzine Flipbook platform, which offers interactive features and easy access via desktop and mobile devices. In conclusion, the transformation of PRFM Radio’s promotional media into a digital e-magazine has proven effective in strengthening brand presence, improving audience engagement, and opening new business opportunities in the digital media landscape